2011
DOI: 10.1177/0960327111403172
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of acute drug poisoning in a tertiary center from Iasi County, Romania

Abstract: The aim of this retrospective epidemiological study was to investigate the demographical, etiological and clinical characteristics of acute drug poisonings in Iasi County, Romania. All patients were referred and admitted in the Toxicology Clinic of “Sf. Ioan” Emergency Clinic Hospital Iasi, Romania. Between 2003 and 2009, 811 cases of acute drug poisonings were recorded, counting for 28.43% from the total number of poisonings. The majority of these poisonings resulted in mild (51.94%) and medium (28.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
23
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 36 publications
11
23
0
3
Order By: Relevance
“…Most studies have shown that female exposure to poisoning was much higher than that of males in the sex distribution of the adult age group (3,6,(9)(10)(11). Similar to the literature, the admissions of females were greater than males in our study (F/M=41/23).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most studies have shown that female exposure to poisoning was much higher than that of males in the sex distribution of the adult age group (3,6,(9)(10)(11). Similar to the literature, the admissions of females were greater than males in our study (F/M=41/23).…”
Section: Discussionsupporting
confidence: 90%
“…In similar studies it is seen that intentional drug ingestions are higher even if the rates show differences (3,10,11,15). However in our study, this rate is a little higher than it is in other studies.…”
Section: Discussionmentioning
confidence: 83%
“…This is consistent with other studies on poisoning in different age groups [19,20]. The most commonly used drugs were benzodiazepines, responsible for the largest proportion of deaths, which is also confirmed by other studies [7,[21][22][23][24]. In our opinion, the large recorded number of cases of benzodiazepine poisoning may reflect their extensive sales and overall use [25,26].…”
Section: Discussionsupporting
confidence: 80%
“…In Romania, epidemiological data suggest that acute drug poisoning in suicide attempts is the most common reason for hospitalization of patients with poisoning (97.27%) and poisoning more frequently occurs due to a combination of drugs (32.92%), with a mortality rate of 0.3%. [26] Self-poisoning with organophosphate pesticides in our area showed a mortality rate of 3.8%. [27] Most of the patients in our study with acute poisoning had attempted suicide, using drugs or a combination of poisons, comparable with the distribution reported in studies from the United States, or Central Europe.…”
Section: Discussionmentioning
confidence: 99%